Температурні зміни енергії екситонного переходу в плоских напівпровідникових наноплівках - Крамар, В. (Праці наукового товариства ім. Шевченка, 2011)
Warm up dependency of the ground state exciton energy in a at semiconductor based nanofilm was studied by Green s function method. The binding energy of exciton and its dependency on the temperature has been evaluated using the Bethe method Numeric calculations for at nanofilms based on the double hetero junction GaAs/AlxGa1-xAs were performed as an example. It is found that the exciton binding energy practically does not depend on the temperature T in the studied nanosystems having a weak electron phonon coupling Energy of the ground state exciton transition de creases with an increase of T according to nonlinear law due to the carrier energy transformations by electron phonon interaction. The scale of the exciton energy warm up changes in a nanofilm depends on its thickness a and has the greatest value in case a =<10 nm.